Grand challenges in entomology - Luke, Sarah H. (2023)
Funding Information: Royal Entomological Society; UKRI Natural Environment Research Council, Grant/Award Number: NE/V006533/1; Rural & Environment Science & Analytical Services Division of the Scottish Government; ; Alexander von Humboldt Foundation; Department of Agriculture, Environment & Rural Affairs; Center for Environmental and Sustainability Research; FCT/MCTES, Grant/Award Number: UID/AMB/04085/2020; UKRI Biotechnology and Biological Sciences Research Council, Grant/Award Number: BBS/E/C/000J0200; UKRI Biotechnology and Biological Sciences Research Council Norwich Research Park Biosciences Doctoral Training Partnership, Grant/Award Number: BB/M011216/1; UKRI Natural Environment Research Council, Grant/Award Number: NE/N014472/2 Funding information Funding Information: This study was approved by the University of Cambridge Psychology Research Ethics Committee (permit number PRE.2020.103). The exercise was funded by the Royal Entomological Society (RES). Helen E. Roy acknowledges support from UK Natural Environment Research Council grant NE/V006533/1 GLobal Insect Threat‐Response Synthesis (GLiTRS): a comprehensive and predictive assessment of the pattern and consequences of insect declines. Lorna J. Cole's time was funded by the Rural & Environment Science & Analytical Services Division of the Scottish Government. Daniel J. Leybourne was supported by the Alexander von Humboldt Foundation through a postdoctoral research fellowship. Sajidha Mohammed thanks the RES for providing 1‐year of free student membership which allowed them to contribute to the workshop. Archie K. Murchie was supported by the Agri‐Food & Biosciences Institute which is sponsored by the Department of Agriculture, Environment & Rural Affairs (NI). Maria‐Rosa Paiva receives support from CENSE (Center for Environmental and Sustainability Research), which is financed by national funds from FCT/MCTES (UID/AMB/04085/2020). Chris R. Shortall was supported by the Rothamsted Insect Survey, a National Capability, which is funded by the Biotechnology and Biological Sciences Research Council under the Core Capability Grant BBS/E/C/000J0200. Christopher D. Williams thanks the Faculty of Science at Liverpool John Moores University for funding attendance at various Royal Entomological Society meetings. Natalia B. Zielonka was supported by the UKRI Biotechnology and Biological Sciences Research Council Norwich Research Park Biosciences Doctoral Training Partnership (BB/M011216/1). Lynn V. Dicks's time was funded by the Natural Environment Research Council (grant code: NE/N014472/2). For the purpose of Open Access, the authors have applied a CC BY public copyright licence to any author accepted manuscript version arising from this submission. We sincerely thank all survey participants for contributing their ideas, knowledge and time. The authors thank four anonymous reviewers, Manu Saunders and Raphael Didham for their comments on an earlier version of the manuscript. For one of our co‐authors and workshop participants, Professor Simon Leather Hon. FRES, this is a posthumous publication. We dedicate this paper to him, as a heartfelt tribute to his incredible contributions to entomological research, higher education and public engagement. Publisher Copyright: © 2023 The Authors. Insect Conservation and Diversity published by John Wiley & Sons Ltd on behalf of Royal Entomological Society.